A minimal moral hazard central stabilisation capacity for the EMU based on world trade - Roel M. W. J. Beetsma; Jacopo Cimadomo; Simone Cima (European Central Bank (ECB), 2018)
Recent debate has focused on the introduction of a central stabilisation capacity as a completing element of the Economic and Monetary Union. Its main objective would be to contribute cushioning country-specific economic shocks, especially when national fiscal stabilisers are run down. There are two main potential objections to such schemes proposed so far: first, they may lead to moral hazard, i.e. weaken the incentives for sound fiscal policies and structural reforms. Second, they may generate permanent transfers among countries. Here we present a scheme that is relatively free from moral hazard, because the transfers are based on changes in world trade in the various sectors. These changes can be considered as largely exogenous, hence independent from an individual government's policy; therefore, the scheme is better protected against manipulation. Our scheme works as follows: if a sector is hit by a bad shock at the world market level, then a country with an economic structure that is skewed towards this sector receives a (one-time) transfer from the other countries. The scheme is designed such that the transfers add up to zero each period, hence obviating the need for a borrowing capacity. We show that the transfers generated by our scheme tend to be countercyclical and larger when economies are less diversified. In addition, since transfers are based on temporary changes in world trade, the danger of permanent transfers from one set of countries to the other countries is effectively ruled out. Finally, we show that transfers are quite robust to revisions in the underlying export data.
Keywords: E32; E62; E63; 330; EMU; central fiscal capacity; exports; moral hazard